Clinical practice during the COVID-19 pandemic: a qualitative study among child and adolescent psychiatrists across the world - Jordan Sibeoni; Emilie Manolios; Emmanuel Costa-Drolon; Jean-Pierre Meunier; Laurence Verneuil; Anne Revah-Levy (BMC, 2021)
Abstract Background The COVID-19 pandemic has directly impacted the field of child and adolescent psychiatry, affecting all aspects of the lives of children and their families and increasing their risk of distress and mental health issues, especially among children with preexisting psychiatric disorders. Child and adolescent psychiatrists (CAPs) across the world have had to adapt their practice, due to lockdown and social distancing measures. This study aimed to explore how CAPs experienced their clinical practice in these singular conditions. Methods This exploratory international qualitative study used the Inductive Process to analyse the Structure of lived Experience (IPSE) approach, which is a five-stage inductive process used to explore the lived experience of participants in depth and to analyze their structure of lived experience. This study took place from March through July 2020 through individual in-depth video interviews. The sample size was determined according to the principles of theoretical sufficiency. Results 39 CAPs from 26 countries participated (age range 32-70 years; 23 women). Data analysis produced a structure of lived experience comprising three central axes of experience: (1) lost in space, lost in time, describing CAPs' experience of disorganization of their clinical practice in the dimensions of lived time and lived space, (2) the body-of CAPs and patients-underlining their disconcerting experience of both sensory aspects and the non-embodied encounter during clinical practice, and (3) unpleasant emotions, with angst and loneliness the two main feelings coloring their clinical practice experience. Conclusions This analysis of the structure of lived experience of CAPs went beyond the sole context of the pandemic and revealed key aspects of what usually organizes CAP clinical practice. It identified two blind spots or conceptual voids within the child and adolescent psychiatry field: first, the intrinsic therapeutic function of a CAP clinical practice and, second, the important diagnostic and therapeutic function of the embodied encounter during CAP consultations. Beyond the context of COVID-19, further research should investigate these aspects to better define what a CAP does in practice and to increase both attractiveness and recruitment in this specialty.